Saneamento básico como fator relacionado às doenças de veiculação hídrica no município de São Cristóvão-SE - Alves, Ana Vanuzia (2019)
The lack of adequate environmental sanitation is one of the main causes of water pollution and contamination for human supply and contributes to the increase in cases of waterborne diseases. Deficiencies in infrastructure and basic services are some of the problems found in the Jardim Rosa Elze neighborhood, located in the municipality of São Cristóvão - SE, which concentrates a high population density. Therefore, the general objective of this work was to evaluate the occurrence of diseases associated with the situation of access to basic sanitation services infrastructure in the population living in the Rosa Elze neighborhood, in São Cristóvão / SE. This was a cross-sectional study that was conducted from 2014 to July 2019. Interviews were conducted through a semi-structured questionnaire; photographic record, with emphasis on observational analytical study; and collection of secondary data through patient records and public information systems. Sample characterization was performed using descriptive analysis and 95% confidence interval. For association of variables, Poisson regression was performed with significance level (p ≤ 0.05). The sample consisted of 458 individuals. There was a higher proportion of residents' perception regarding floods / floods and occupation of areas in preservation / permanent. Participants reported changes in publicly available water, mainly in color and then smell. In addition, the street presents itself as the main destination for sewers. By associating the occurrence of water-borne diseases with independent factors, it was noted that those who reported no change in water quality were 46% less likely to have water-related diseases. Those who did not have a pit at home were more likely to have water-related illnesses. Based on the data analysis it was concluded that waterborne diseases can be prevented with adequate basic sanitation conditions. Thus, the development of new studies aiming at the importance of basic sanitation to public health becomes necessary. It is hoped that the collected data will serve as subsidy so that effective preventive measures can be carried out that contribute to the reduction of disease rates and to the improvement of the population's health conditions.